Defective RNA Polymerase III sensing of mitochondrial DNA in pulmonary epithelial cells impairs type I IFN immunity to SARS-CoV-2 - Michelle Møhlenberg; Sofie Eg Jørgensen; Renée Marije van der Sluis; Thomas Zillinger; Daniëla Maria Hinke; Anne Kruse Hollensen; Anne Louise Hansen; Pierre Hausfater; Guy Gorochov; Florence Tubach; Jade Ghosn; Cedric Laouenan; et al. (Proceedings of the National Academy of Sciences, 2026)
The clinical spectrum of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection ranges from asymptomatic cases to critical COVID-19 pneumonia. To investigate the role of host genetics in susceptibility to critical COVID-19 and identify pathophysiological mechanisms and pathways, we analyzed whole-exome and whole-genome sequencing data from the COVID Human Genetic Effort. We identified 10 rare, monoallelic predicted loss-of-function variants in 18 patients in POLR3A and POLR3C encoding two subunits of RNA polymerase III (POL III), a nuclear multisubunit enzyme, which has been implicated in cytosolic DNA sensing. These variants were deleterious for expression of full-length POLR3A and POLR3C proteins. We demonstrate that human pulmonary A549-hACE2 cells with reduced POLR3A or POLR3C expression exhibit impaired type I IFN responses to transfected mitochondrial DNA (mtDNA) or SARS-CoV-2 infection, together with increased viral replication. Mechanistically, we show that SARS-CoV-2 induces cellular mtDNA release via oligomerization of the mitochondrial voltage-dependent anion channel under virus-induced oxidative stress, enabling POL III–mtDNA interaction. These findings establish POL III as a sensor of endogenous mtDNA released during viral infection and indicate that autosomal dominant POL III haploinsufficiency may predispose individuals to critical COVID-19.